2006
DOI: 10.1097/01.ijg.0000212213.18018.8f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Written Instructions on Accuracy of Self-Reporting Medication Regimen in Glaucoma Patients

Abstract: The education level of the patient and the number of medications showed direct correlation with patients' ability to report medications accurately. Patients showed improvement in accuracy of reporting medications when given written instructions about their regimen, regardless of their level of education or number of medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 8 publications
0
19
0
2
Order By: Relevance
“…Newer dosing aids combine alarm features with a dosing lever, and register adherence data [42,43]. Others suggest written instructions as a simple and inexpensive intervention, as written instructions improved the accuracy of self-reporting medication regimen [44]. Medication reviews are also seen as a tool for improving adherence [45].…”
Section: Discussionmentioning
confidence: 99%
“…Newer dosing aids combine alarm features with a dosing lever, and register adherence data [42,43]. Others suggest written instructions as a simple and inexpensive intervention, as written instructions improved the accuracy of self-reporting medication regimen [44]. Medication reviews are also seen as a tool for improving adherence [45].…”
Section: Discussionmentioning
confidence: 99%
“…21 Self reported estimates of adherence are also unreliable with patients tending to overestimate their adherence rates. 13,22 A study undertaken by Kass et al 21 showed the 30-day patient recorded adherence rate in a medication log to be 99%, significantly higher than the rate of 76% measured by an eye drop monitor. Furthermore, physicians were unable to accurately identify, which patients had adherence rates of o50% compared to 490%.…”
Section: Discussionmentioning
confidence: 99%
“…In an intervention study to improve the adherence of glaucoma patients with poor health literacy, only 42% of patients who did not complete high school were initially able to accurately answer questions about their medications, compared with 79% of patients who had completed high school. (Kharod et al, 2006;Tsai et al, 2009) After receiving written instructions about their medication regimen, 88% of patients in the former group and 96% of patients in the latter group were able to accurately answer questions about their treatment. Different types of educational programs have been designed to enhance patient knowledge.…”
Section: Methods For Improving Adherencementioning
confidence: 99%